(3LQjeI LdH GdeNOQGJ hWQb ehGLgJgG (B: s (3OQGSI ebGQfI (B/ s - (3YGOd eMeO YHOGdYRjR GdShjOjs; (3eCehf eMeO SdGegs; (3eMehO SdjeGf cHjT s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3JeKd OQGSI LQjeI LdH GdeNOQGJ hWQb ecGaMJgG (B: (3OQGSI ebGQfI GgejI HGdZI HGdfSHI dNWhQJgG hGdGVQGQ GdJi JQJH YfgG (B: (3MjK jfUQa VQQgG Gdi eLGdGJ GdMjGI GdYGeI (B: (3GdGbJUGOjI hGdGLJeGYjI hGdKbGajI hGdUMjI Pdc Gf JaTi GdeNOQGJ hGfJTGQgG ai Gi eLJeY (B: (3QgfG HHYV GdGaYGd GdGLQGejI eKd GdGSJjQGO hLdH GdeNOQGJ hfbdgG (B: (3hgPG jYfi Gf LdH GdeNOQGJ jSge ai GfJTGQ GdeNOQGJ Ydi GdeSJhjjf GdeMdi hGdOhdj (B: (3hjfTW ai gPG GdGJLGg GdLeGYGJ Gh eG JYQa HGdeGajG (B: (3hjJeKd gPG GdfTGW HeG jYQa HGdLQjeI GdefXeI Gh GdLQjeI YHQ GdhWfjI ; hdPdc JJQJH GgejI GdOQGSI ef GdGgJeGe GdeMdi hGdGbdjei ai ecGaMI LQGFe GdeNOQGJ HUhQI YGeI hLQjeI LdH GdeNOQGJ HUhQI NGUIs
(3jTJed Ydi edGMb(B: (3UaMI (B526-586s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2006s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B587-600s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGaYGd GdGLQGejIs; (3GdLQjeI YHQ GdhWfjIs; (3GdeNOQGJs; (3TQYjI JLQje LdH GdeNOQGJs; (3eLGdGJ GHGMI LdH GdeNOQGJs; (3GdVHW GdbVGFis; (3GdJLQje GdefXe ai LdH GdeNOQGJs; (3LQjeI ZSjd GdGehGds; (3GLQGAGJ ecGaMI GdLQjeI OhdjkGs; (3JSdje GdeLQejfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs